Composition for preventing cardiovascular diseases - Ismail, Maznah; Nadarajan, Sarega (2014)
The present invention relates to a composition comprising extracts of a plant in the family Acanthaceae. More particularly, the composition comprises Clinacanthus nutans, which is a species of the family Acanthaceae. The composition is capable of lowering cholesterol and oxidative stress as well as increasing hydroxyl radical scavenging activity. According to the present invention, the composition comprising the Clinacanthus nutans extracts is used for manufacturing a medicament, as a food product or a beverage product in order to prevent cardiovascular disease.